2016
DOI: 10.1007/s10571-016-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Negatively Regulates ATP-TLR4-Activated Inflammasome in Microglia

Abstract: During acute brain injury and/or sterile inflammation, release of danger-associated molecular patterns (DAMPs) activates pattern recognition receptors (PRRs). Microglial toll-like receptor (TLR)-4 activated by DAMPs potentiates neuroinflammation through inflammasome-induced IL-1β and pathogenic Th17 polarization which critically influences brain injury. TLR4 activation accompanies increased CD40, a cognate costimulatory molecule, involved in microglia-mediated immune responses in the brain. During brain injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Our data suggest that astrocytes but not microglia are the main cells of the central nervous system (CNS) responsible for the pro-inflammatory milieu occurring during the early phase of epileptogenesis, corroborating previous published data (Ravizza and Vezzani, 2006;Ravizza et al, 2008). Moreover, a recent study demonstrated that expression of CD40 by microglia is able to decrease IL-1b secretion and consequently negatively regulates neurotoxic inflammasome activation during sterile inflammation (Gaikwad et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data suggest that astrocytes but not microglia are the main cells of the central nervous system (CNS) responsible for the pro-inflammatory milieu occurring during the early phase of epileptogenesis, corroborating previous published data (Ravizza and Vezzani, 2006;Ravizza et al, 2008). Moreover, a recent study demonstrated that expression of CD40 by microglia is able to decrease IL-1b secretion and consequently negatively regulates neurotoxic inflammasome activation during sterile inflammation (Gaikwad et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with data showing that microglia express IL-1b in the first 4 h after SE but not at later time-points where astrocytes drive inflammation during early epileptogenesis (Ravizza et al, 2008). Moreover, a recent study demonstrated that expression of CD40 by microglia is able to decrease IL-1b secretion and consequently negatively regulates neurotoxic inflammasome activation during sterile inflammation (Gaikwad et al, 2016). IL-1b is thought to contribute to neuronal hyperexcitability and excitotoxicity through potentiation of glutamatergic neurotransmission (Hu et al, 2000;Lai et al, 2006;Viviani et al, 2003;Ye and Sontheimer, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…An important adaptive immune cytokine, IFN‐γ, exerts a regulatory effect on IL‐1 production and immunopathological responses through generation of nitric oxide, which inhibits the NLRP3 inflammasome assembly via nitrosylation of the NLRP3 protein 34 . CD40, a costimulatory molecule, exhibits an inhibitory function in ATP‐Toll‐like receptor 4‐mediated inflammasome activation in microglia 35 . IFN‐γ‐mediated CD40 expression leads to decreased production of IL‐1β and suppresses the neurotoxic inflammasome activation required for pathogenic Th17 polarization 35 .…”
Section: Negative Regulators Of Nlrp3 Inflammasome Complexesmentioning
confidence: 99%
“…CD40, a costimulatory molecule, exhibits an inhibitory function in ATP‐Toll‐like receptor 4‐mediated inflammasome activation in microglia 35 . IFN‐γ‐mediated CD40 expression leads to decreased production of IL‐1β and suppresses the neurotoxic inflammasome activation required for pathogenic Th17 polarization 35 . These findings corroborate results from another study, which found that increased nitric oxide in TXNIP‐deficient mice exerted a negative effect on excessive inflammatory responses and inflammasome activation during endotoxic shock through induction of S ‐nitrosylation of NLRP3 36 .…”
Section: Negative Regulators Of Nlrp3 Inflammasome Complexesmentioning
confidence: 99%
“…It is also widely accepted that TLR4 is activated by other agonists including damageassociated molecular patterns, viral proteins and transition metals (4)(5)(6)(7)(8). TLR4 was found to mediate immune hypersensitivity reactions to the Group 9/10 transition metals nickel, cobalt and palladium (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%